ESTIMATION OF NITROGEN DIOXIDE (NO2) CONCENTRATION USING FENGYUN-4A DUST STORM DETECTION (FY-4A DSD) PRODUCT DURING THE COVID-19 LOCKDOWN IN METRO MANILA, PHILIPPINES - K. A. Solidum; J. A. Principe; M. R. C. O. Ang (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2021)
The coronavirus disease was discovered in 2019 (COVID-19) and was eventually declared by the World Health Organization (WHO) as a global pandemic on March 11, 2020. This study aims to determine the correlation of Dust Storm Detection (DSD) index from the Fengyun-4A (FY-4A) data, NO2 ground observations, and daily positivity rate of COVID-19 cases in Metro Manila and predict the confirmed daily cases of COVID-19 using the established correlations. FY-4A DSD products were used to obtain different Dust Storm Indices (DSI) and daily COVID-19 confirmed cases were tallied during the period November 01–30, 2020, and March 01–31, 2021. Ground-observed NO2 levels from Environmental Management Bureau (EMB) monitoring stations were gathered for validation and regression analysis. Results of linear regression analysis between the DSI and NO2 exhibited a weak correlation (0.24) with the available observations at the specified period. Ground-observed NO2 levels exhibit the same trend with the daily positivity rate of COVID-19 considering only a smaller area and short period of observations. Moreover, results showed a weak correlation (0.07) between the positivity rate of COVID-19 case as a function of the DSD Index and ground-observed NO2 levels. Uncertainty of results from this study may be attributed to the fact that it has focused on a relatively small area due to limited available ground observations. Therefore, it is recommended to apply the same analysis on different periods of observations using as many NO2 level ground observations as available and determine if variables follow the same trend and correlations as reported in this study.